Depression Levels Among Nursing Students: A Descriptive Study - Tunggal, Deif; syahrir, Syahrir; Asa, Halena Meldy; Jannah, Insani Fitrahulil; Riwu, Audrey Gracelia (Universitas Nusa Cendana, 2024)
Background : Depression is one of the most common mental health disorders and a serious global concern, particularly among university students. Nursing students are highly vulnerable to depression due to academic pressure, professional expectations, and the challenges of clinical and social environments. Objective : This study aimed to assess the level of depression among nursing students at Nusantara Institute of Health Sciences as a foundation for developing targeted mental health interventions. Methods : This research employed a descriptive quantitative design with 55 participants selected using purposive sampling. The instrument used was the Indonesian-validated version of the Patient Health Questionnaire-9 (PHQ-9). Data were analyzed using SPSS version 20.0. The results showed that the majority of respondents were over 20 years old (52.7%), female (67.3%), lived in boarding houses (67.3%), and were self-motivated to pursue nursing education (76.4%). Based on PHQ-9 scoring, 49.1% of the participants experienced mild depression, 9.1% moderate depression, 3.6% moderately severe depression, and 38.2% had no signs of depression. Conclusion: These findings indicate that although most respondents had intrinsic motivation and independent living conditions, mild depressive symptoms remained prevalent. Therefore, early detection and preventive mental health interventions are essential to support academic success and future professionalism among nursing students. Keywords: Depression, Nursing Students, PHQ-9, Mental Health, Early Detection.